Method for producing rigid polymethyl methacrylate foams as core materials in rotor blades of wind power generation apparatus and in boat construction

By adopting PMMA hard foam with high glass transition temperature and uniform pore structure, the problem of high viscosity absorption and processing temperature limit of PET and PVC hard foam in wind power generation equipment and ship construction is solved, lower viscosity absorption and higher processing temperature are achieved, improving product quality and reducing costs.

JP2025069308APending Publication Date: 2025-04-30EVONIK OPERATIONS GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2025015501
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-08-08
Filing Date
2025-01-31
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Existing PET and PVC hard foams have problems with high viscosity absorption and processing temperature limitations in wind power equipment and ship construction, resulting in high cost and poor quality.

Method used

Polymethylpropionate (PMMA)-based hard foam was used, which had a glass transition temperature (Tg) of more than 110°C by dynamic mechanical thermal analysis (DMTA), and a uniform pore structure of 50-300 μm was formed by adding silicon oxidized particles as nuclearizing agent.

Benefits of technology

PMMA hard foam significantly reduces adhesive absorption, improves processing temperature limits, ensures high-quality outer layers and core materials, while reducing the quality and cost of the final product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069308000001
    Figure 2025069308000001
  • Figure 2025069308000002
    Figure 2025069308000002
Patent Text Reader

Abstract

To provide use of polymethyl methacrylate-based rigid foams as a core material in sandwich components in rotor blades of wind power generation apparatuses and in boat construction.SOLUTION: A blowing agent-laden polymer composition is foamed to afford polymethyl methacrylate-based rigid foams having an average pore size in the range from 50 to 300 μm measured according to ASTM D3576 (published in 2015).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polymethyl methacrylate-based rigid foam in sandwich components for use in wind power equipment and boat construction, having a glass transition temperature Tg determined by DMTA measurement according to standard ISO 6721-7 above 110°C, characterized by foaming a polymer composition with a blowing agent to obtain a foam material having an average pore size in the range of 50 to 300 μm, measured according to ASTM D3576. [Background technology]

[0002] Sandwich composites consist of a core material and an outer layer placed on it. In general, these sandwich composites are distinguished by their high component stiffness with a low mass. In this case, the core material must meet various requirements, for example, it must be firmly bonded to the outer layer so that it can transmit shear forces. Furthermore, the core material should have the lowest possible density.

[0003] Often utilized core materials are rigid foams due to their low density.

[0004] To produce the sandwich composite, an outer layer is usually placed on the core material and impregnated with resin or a fiber material impregnated with resin but not yet cured (prepreg). In a second step, the resin is then cured in the outer layer, during which bonding to the core material also occurs. The curing is carried out at elevated temperature and pressure to ensure that the outer layer is present without defects and that it is well bonded to the core material. In this case, the resin of the outer layer is bonded to the core material by various mechanisms. This can be adhesion / cohesion or chemical bonding of the resin to the outer layer. Furthermore, resin that still has a certain degree of fluidity before the curing can also flow in the open cells on the surface of the foam core, thus resulting in a bond between the outer layer and the core material by form-fitting after the curing ("interlocking").

[0005] The higher the temperature and pressure used in curing the outer layer, the faster the curing can usually be accomplished.

[0006] The sandwich composites mentioned above are widely used in the assembly of wind turbine blades as well as in boat construction. The core materials used in these fields are mainly rigid foams due to their low density. In particular, PVC and PET-based foams are used for these applications. Examples of these are Airex C70.55 (PVC) from 3A Composites, Airex T10.100 (PET), GPET 115 (PET) from GURIT, Divinicell H from DIAB or ArmaFORM (PET) from Armacell.

[0007] What is important here is that a certain level of compressive strength and heat distortion resistance must be achieved in order to allow the manufacturing process of the component. The mechanical strength of foams made of the same base polymer decreases with density, so that only densities up to a certain lower limit can be used depending on the base polymer of the foam. In the case of PET-based foams, this lower limit is about twice the density of PVC-based foams. Here, PVC-based foams have a clear advantage over PET foams. On the other hand, PET foams have an advantage over PVC foams in terms of the cost of the core material.

[0008] A further factor of the final component mass of the sandwich composite is the resin absorption of the foam. Resin absorption is understood to be the inflow of the still liquid resin of the outer layer before curing into the open pores on the surface. This resin absorption is necessary to obtain a shape bond of the outer layer to the core material and thus a good adhesion. It is advantageous that only the minimum amount of resin necessary for a good bond is absorbed by the uppermost open pores of the foam, since due to its high density, the resin would otherwise contribute unnecessarily to the total mass of the final component.

[0009] Problem As mentioned above, the core materials typically used in wind turbine rotor blades and in boat construction are rigid foams based on PVC or PET. However, these rigid foams have some obvious disadvantages.

[0010] One drawback is the high resin absorption in the case of both foams, which leads to unnecessarily high resin being absorbed by the foam, which on the one hand leads to unnecessarily high costs due to the resin used, and on the other hand increases the final component weight.

[0011] A further disadvantage of PET and PVC foams for these applications is that the possible processing temperatures in the production methods of the sandwich composites are limited to about 80° C., since above these temperatures the mechanical properties of the PET and PVC rigid foams significantly decrease and make a high-quality production process no longer possible (deformation of the core material).

[0012] The challenge was therefore to find a core material for the above applications which a) has a lower resin uptake in order to save costs and mass, and b) which at the same time also allows for higher process temperatures.

[0013] Solution The problem is solved by providing a method for producing a polymethyl methacrylate-based rigid foam in sandwich components for use in wind power equipment and boat construction, having a glass transition temperature Tg above 110°C, determined by DMTA (Dynamic Mechanical Thermal Analysis) measurements according to standard ISO 6721-7 (published August 2005), characterized by foaming a polymer composition with a blowing agent to obtain a foam material having an average pore size in the range of 50 to 300 μm, measured according to ASTM D3576 (published 2015).

[0014] It has been found that polymethyl methacrylate (PMMA) based rigid foams meet the above requirements of low resin uptake and higher process temperatures compared to competitive PET and PVC foams. What is particularly surprising here is that the outer layer bond is extremely good in the case of PMMA foams, despite the significantly lower resin uptake.

[0015] 0.03g / cm3 as measured by VARI (vacuum-assisted resin infusion) 2 The low resin uptake, having less than 1000 ppm, distinguishes the rigid foams according to the invention from the competitive PET and PVC based systems mentioned above.

[0016] With the present invention, all pore sizes in the range of 50 to 300 μm and pore sizes in the range of 30 to 500 kg / m, measured according to DIN EN ISO 1183 (issued April 2013), 3 , preferably 250 kg / m 3 A PMMA-based foam is provided having a foam density of less than 1000 nm.

[0017] A suitable method for producing PMMA foams, in which the foams are produced by polymerization, for example slab polymerization of a monomer mixture containing mainly MMA and / or a syrup consisting of a polymer mainly or entirely consisting of MMA and a monomer mixture mainly or entirely composed of MMA, in the presence of a blowing agent and a nucleating agent which are non-gaseous under the polymerization conditions, is described, for example, in EP 3277748. In a second step, the thus obtained completely polymerized PMMA slab with blowing agent is then foamed by heating, in which case small and uniform pores are formed due to the addition of the nucleating agent.

[0018] The method is particularly characterized in that the nucleating agent comprises silicon oxide particles having a diameter of 4 to 1000 nm. The composition then contains 0.01 to 2.0% by weight, preferably 0.2 to 1.5% by weight, of one or more initiators, 2 to 20% by weight, preferably 3 to 15% by weight, of one or more blowing agents, 0.2 to 10% by weight, preferably 0.5 to 8% by weight, of silicon oxide particles having a diameter of 4 to 1000 nm, preferably 5 to 500 nm, and 70 to 97.79% by weight, preferably 75 to 97.8% by weight, of a polymer-forming mixture, where the polymer-forming mixture consists of at least 75 mol % methyl methacrylate (MMA) and / or MMA repeat units and 0 to 80% by weight, preferably 0 to 50% by weight, of which may be present as polymers and / or oligomers. The composition is first polymerized at a temperature between 20° C. and 100° C., preferably between 30° C. and 70° C., and subsequently foamed at a temperature between 130° C. and 250° C., preferably between 150° C. and 230° C. In addition to the components mentioned, the composition may contain up to 27.79% by weight of further components. Examples of these further components are, in particular, further polymer components which are not MMA-containing polymers, UV stabilizers, fillers and pigments.

[0019] The silicon oxide particles are preferably SiO2 particles. However, it is also possible that these particles have a stoichiometric composition that is not strictly 1:2. And, especially in the case of very small particles, there may be deviations from the stoichiometric composition of up to 30%. Also, up to 20% of the silicon may be replaced by other metal ions, such as aluminum. According to the invention, it is only important that the stoichiometric ratio of silicon to oxygen is 0.7-1.3:2 and that the non-oxygen atoms in the particles are at least 80 mol% silicon. However, other nucleating agents, such as talc, layered silicates, graphene, graphite oxide, Al2O3, polymer particles that are immiscible or insoluble in the monomer mixture, etc., can also be used. If the pore size is within the range described without the nucleating agent, the nucleating agent can be omitted.

[0020] The polymer-forming mixture may have up to 25% by weight of further components in addition to the MMA. These further components may include monomers copolymerizable with MMA, chain transfer agents and / or crosslinking agents. In this case, the MMA and the above-mentioned copolymerizable monomers can be used completely as monomers. The polymer-forming composition may in particular contain up to 0.5% by weight of crosslinking agent and / or up to 1.5% by weight of chain transfer agent.

[0021] However, in a more easily handled embodiment of the present invention, the MMA and the copolymerizable monomers may also be present as polymers and / or oligomers in a proportion of up to 80% by weight, preferably up to 50% by weight. The advantage of such a syrup consisting of monomers and polymers or oligomers is that it has a higher viscosity than a pure monomer mixture and thus the total amount of energy released during the polymerization is less.

[0022] Said monomer copolymerizable with MMA can be especially acrylate, for example especially methyl acrylate, ethyl acrylate, propyl acrylate or n-butyl acrylate. The copolymerization of acrylate additionally stabilizes the foam, especially at high foaming temperatures, because these foaming temperatures can be above the ceiling temperature of pure MMA. If no stabilizing comonomer is incorporated, shorter foaming times or correspondingly lower foaming temperatures should be preferred.

[0023] Further examples of suitable comonomers are (meth)acrylic acid, methacrylates such as ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, tert-butyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, styrene, (meth)acrylamide, N-alkyl (meth)acrylamides having 1 to 12 carbon atoms in the alkyl group, hydroxyl alkyl (meth)acrylates having 1 to 4 carbon atoms in the alkyl group, polyether (meth)acrylates, where the polyethers may have a molecular weight of 200 to 5000. The comonomers may then be present as a mixture of at least two of these comonomers. If these comonomers include n-butyl (meth)acrylate and / or n-propyl (meth)acrylate, their proportion in the overall composition cannot exceed 3% by weight in total. If crosslinkers are used, these are preferably di(meth)acrylates, tri(meth)acrylates or tetra(meth)acrylates, allyl(meth)acrylates, triallyl cyanurates, triallyl isocyanurates or mixtures containing at least two of these crosslinkers.

[0024] The notation (meth)acrylate here means both methacrylates, such as methyl methacrylate, ethyl methacrylate, etc., as well as acrylates, such as methyl acrylate, ethyl acrylate, etc., as well as mixtures of both.

[0025] If chain transfer agents are used, they are preferably compounds having 1 to 5 mercaptan groups, γ-terpinene or a mixture of at least two of these chain transfer agents. Particularly preferred are pentaerythritol tetrathioglycolate, 2-mercaptoethanol, alkyl mercaptans having 2 to 12 carbon atoms, thioglycolic acid, thioglycolate, γ-terpinene or a mixture of at least two of these chain transfer agents.

[0026] A particularly important aspect of the present invention is the use of said nucleating agent in said foamable composition. This use of a nucleating agent in the production of PMMA foam, which is novel compared to the prior art, surprisingly results in PMMA foams having particularly small and uniform as well as uniformly distributed pores being obtained. The microporosity thus obtained is of great importance for a variety of applications. In insulation applications, generally, for the same density and the same cell gas, the insulating effect of a foam increases as the pore size decreases. In lightweight construction applications, where a resin-impregnated outer layer is placed on a foam core, a low resin absorption of the foam core is important for weight reduction. The finer the pores of the closed-cell foams used for this purpose, the less resin can be absorbed.

[0027] It has been surprisingly found that when silicon oxide particles are used, a significantly microcellular foam can be achieved compared to foams based on a base formulation without nucleating agent. Thus, for example, AEROSIL OX50 (EVONIK Industries AG) can be used to obtain a very microcellular foam. Surprisingly, it has also been found that such an effect was not achieved using other additives, such as talc powder, which can potentially also have a nucleating effect. On the contrary, the use of talc made foaming rather difficult and a very inhomogeneous foam was obtained. The use of Al2O3 particles (AEROXIDE ALU C, EVONIK Industries AG) also did not produce results, since foaming was not possible here. This shows that the introduction of any particles in the presently presented production method of PMMA foams alone does not bring about the desired degree of porosity improvement, but rather surprisingly, first of all, only silicon oxide particles seem to be suitable for this purpose.

[0028] Furthermore, the PMMA foams produced according to the invention have surprisingly high strength and at the same time surprisingly low brittleness and can therefore be used, for example, in lightweight constructions. Furthermore, due to their good material properties, it is possible to dispense with the use of plasticizers, such as longer-chain alkyl (meth)acrylates or phthalates, which according to previous knowledge have a favorable effect on the flowability or foamability of the PMMA foam, but which at the same time have a detrimental effect on the mechanical properties, especially the strength, of the PMMA foam.

[0029] Particularly suitable blowing agents are tert-butanol, n-heptane, MTBE, methyl ethyl ketone, alcohols having 1 to 4 carbon atoms, water, methylal, urea, isopropyl (meth)acrylate and / or tert-butyl (meth)acrylate. In this case, when isopropyl (meth)acrylate and / or tert-butyl (meth)acrylate are used, they are simultaneously components of the monomer composition mentioned and are first polymerized into the polymer formed during the polymerization in whole or in part. During the foaming, (meth)acrylic acid repeat units are subsequently formed in the polymer, with the elimination of propene or isobutene. In a special embodiment, polymers made from a large proportion of these monomers or entirely from these monomers can also be used. By using such polymerizable or polymerized comonomers that release blowing agents, it is possible, for example, to obtain particularly small and regular pores.

[0030] Particularly suitable blowing agents are tert-butyl (meth)acrylate, isopropyl (meth)acrylate, tert-butanol, isopropanol, tert-butyl methyl ether and poly(tert-butyl (meth)acrylate).

[0031] The polymerization is preferably carried out in a molded container, in particular in the form of a chamber polymerization between two plates, for example glass plates. It can be, for example, a rectangular tank in the simplest case. Polymerization in such a tank subsequently gives plates whose thickness is determined by the filling level of the tank or the plate spacing. However, more complex shapes are also conceivable as containers. The polymerization is preferably carried out at a temperature of 30-70° C. In addition to the generally known radical initiators, for example peroxide or azo initiators, redox systems or UV initiators can also be used as initiators. Polymerization temperatures below 40° C. apply in particular to these redox systems and UV initiators. The UV initiators are initiated by irradiation with the corresponding UV light, whereas the redox initiators include two-component systems, the initiation of which is carried out by mixing both components and the monomer.

[0032] The foaming can then be carried out in the same container, where the volume increase is then limited to one direction, the open side of the container. However, the polymerized material can also be foamed by exposure. Preferably, the foaming is carried out in an oven. Alternatively, the foaming can also be caused by irradiation with infrared radiation, in particular infrared radiation with a wavelength of 0.78 to 2.20 μm, preferably 1.20 to 1.40 μm. A further option is foaming with microwaves. A combination of different methods, such as infrared radiation, microwaves and / or heating in an oven, is also conceivable.

[0033] The foaming and the preliminary polymerization can each be carried out in several temperature steps. By increasing the temperature later during the polymerization, the conversion can additionally increase and the residual monomer content can decrease accordingly. During the foaming, the foaming temperature can be increased stepwise to affect the pore distribution, the pore size and the number of pores.

[0034] Optionally, the method can also be carried out so that the polymerization is carried out only incompletely, in this case preferably to at least 80% conversion, and the final polymerization completion is carried out during the foaming. Such a method has the advantage that at the beginning of the foaming process, the remaining monomers have a plasticizing effect, and no plasticizing compounds will remain in the finished foam. Therefore, in such an embodiment, the polymerization and the foaming will be carried out partly at the foaming temperature simultaneously.

[0035] In addition to the process according to the invention, PMMA foams which can be produced, for example, by such a process are also constituents of the present invention. Such PMMA foams are characterized in that the solids content of the foam comprises 72-98% by weight of polymer with at least 75 mol % MMA repeat units and 0.2-12.5% ​​by weight of silicon oxide particles. Furthermore, the foams have a solids content of 25-250 kg / m, measured according to DIN EN ISO 1183. 3 , preferably 40 to 250 kg / m 3 and an average pore size of less than 500 μm. Preferably, all pore sizes are less than 500 μm.

[0036] The pore size is determined according to standard ASTM D 3576 with the following differences from this standard: firstly, the fracture edge of the PMMA foam is observed, not the knife cut surface. Furthermore, the evaluation is based on the relatively small pores and is not carried out by optical microscopy, but through SEM measurements. However, the calculation of the pore size from the obtained images then follows the standard.

[0037] Preferred are polymers, especially PMMA foams, formed from MMA, an initiator, one or more crosslinkers selected from di(meth)acrylates, tri(meth)acrylates or tetra(meth)acrylates, allyl(meth)acrylates, triallyl cyanurate and / or triallyl isocyanurate, and one or more chain transfer agents.

[0038] The PMMA foam has a resin absorption of 0.03-0.06 g / cm as measured by VARI. 2 0.01-0.03g / cm compared to typical PET and PVC foams which have 2 , preferably 0.02 g / cm 2 The resin absorption amount is shown.

[0039] At the same time, the overcoat adhesion is excellent, which is surprising since good overcoat adhesion would not have been predicted based on the relatively small pores and the associated potentially poorer "interlock" between the foam and the cured resin.

[0040] It has further been found that PMMA-based foams have a higher glass transition temperature than PVC and PET foams. The glass transition temperature of PMMA-based foams, determined by DMTA measurement according to standard ISO 6721-7, is at least 110°C, preferably at least 130°C. This also allows for higher temperatures during the curing process, which can shorten the process time and thus be more cost-effective. It has been found that the curing of the resin during the production of sandwich components can be carried out at temperatures above 110°C, preferably above 120°C. This is not possible in the case of conventional foaming, since decomposition and / or softening already occurs at these temperatures.

[0041] Curing of the resin during the production of the sandwich components at temperatures >110° C. is effected by heating or irradiating the mould.

[0042] Curing of the resin can be carried out in an electrically heatable mould or by using a mould through which a fluid (eg steam) is flowed.

[0043] Curing of the resin by irradiation is carried out by means of infrared or microwave radiation.

[0044] Furthermore, the sandwich components according to the invention can be produced under increased pressure. In this case, a pressing or autoclave process is used. In this case, a fiber layer is inserted into a mold, the foam core is placed, and a further fiber layer is placed. Depending on the variant, a pressure of ≧1 bar or a vacuum is applied, and the resin is injected or sucked in.

[0045] The polymethyl methacrylate-based rigid foam can be used in sandwich materials where special requirements are imposed on the mass. The reduced resin absorption results in a low mass, which makes the sandwich material thus produced particularly suitable for applications where good bonding adhesion at low mass is required. This also results in lower costs in terms of the consumption of the resin used. Furthermore, the investigated PMMA foam allows potentially higher process temperatures and therefore process time savings due to its higher heat distortion resistance.

[0046] The polymethyl methacrylate-based rigid foams are suitable as weather-resistant insulating materials, core materials for sandwich composites, in lightweight construction, as packaging materials, as energy absorbers in crash elements, in building construction elements, as diffusers in lighting engineering applications, in furniture assembly, in boat building, in vehicle manufacturing, in the aviation industry or in model building, especially as core material in rotor blades in wind power plants. EXAMPLES

[0047] Resin absorption amount Materials used: PVC foam: Airex C70.55 from 3A Composites, Steinhausen, Zug (Switzerland) PET foam: Airex T10.100 from 3A Composites, Steinhausen, Zug (Switzerland) PMMA foam: ROHACRYL55 from Evonik Resource Efficiency GmbH, Germany The resin uptake of the core material has to be determined experimentally by VARI (Vacuum Assisted Resin Infusion). For the measurement, a minimum dimension of the sample plate of 300 x 300 mm was specified.

[0048] Before the infusion, the sample size and sample mass must be adjusted to a measurement accuracy of ±0.01 mm and ±0.01 g to determine the sample density and the unit area mass. Since the viscosity of the resin is highly dependent on the temperature, the test apparatus is preheated to 30° C. to ensure constant conditions. The tightness of the test apparatus is tested by a vacuum test, in which the inlet and outlet are clamped and the vacuum loss is controlled after 30 min.

[0049] Furthermore, the resin components should be degassed. This is done by evacuating the resin and hardener in a vacuum at -0.8 bar and 40°C for 60 min. Before mixing, both components must be cooled to room temperature so that the reaction can be started in a controlled manner. Subsequently, a second degassing of the resin system is carried out at -0.8 bar and 40°C for 10 min. When the vacuum test of the test device is completed, the infusion can start. A vacuum should be drawn until the resin is cured. After the infusion is completed, the resin system should be cured at 30°C for at least 18 hours.

[0050] Finally, the edges are cut at right angles to trim the shape, and the peel ply is removed. The difference in mass per unit area between the dry foam plate and the injected foam plate is the resin absorption.

[0051] The resulting values ​​for resin uptake are shown in the following table: [Table 1]

[0052] Outer layer adhesion According to the standard test Drum Peel Test (DIN 53295), the sandwich plate is clamped at the protruding part of the outer layer into a known test device. Using a clamping tool, the outer layer is gripped at the protruding part and removed from the core material at a constant machine speed. The force required for this is recorded. This gives information about the outer layer adhesion.

[0053] In the experiments carried out, failure of the foam material occurred: cohesive failure in the adhesive layer (resin layer) instead of adhesive failure (separation of the foam core and outer layer) is an indication of good outer layer adhesion.

[0054] Thus, sufficient outer layer adhesion to the PMMA foam core is demonstrated.

[0055] In a separate test method, outer layer adhesion is also measured.

[0056] The flatwise tensile test (ASTM C297) starts with a 50x50mm specimen. The specimen consists of a foam core and upper and lower outer layers of resin layers. The specimen is clamped into a tensile device. The upper clamp is pulled at a constant tensile speed.

[0057] In experiments carried out, the foam core was pulled to failure and no delamination of the outer layer from the core material above the resin layer could be detected.

[0058] Thus, sufficient outer layer adhesion is demonstrated.

[0059] Measurement of glass transition temperature for evaluation of heat distortion resistance The Tg values ​​were determined by DMTA measurements according to ISO 6721-7. The following values ​​were found: [Table 2]

[0060] Curing at elevated temperatures The foam core is provided with the outer layer and injected with epoxy resin. In a closed mold, the material is heated to 110° C. The crosslinking is accelerated by the elevated temperature.

[0061] Relatively short cycle times were determined: in the case of a comparative experiment carried out at room temperature, the curing time was over 24 h; the curing process here could be shortened to 20 min at a temperature of 110° C.

[0062] The embodiments of the present invention are as follows: 1. A process for the production of polymethyl methacrylate-based rigid foams in sandwich components for use in wind power plants and in boat construction, having a glass transition temperature Tg above 110°C, determined by DMTA measurement according to standard ISO 6721-7, characterized in that a polymer composition with a blowing agent is foamed to obtain a foam material having an average pore size in the range of 50 to 300 μm, measured according to ASTM D3576. 2. The resin absorption of the foam material is 0.01 to 0.03 g / cm as measured by VARI. 2 1. The method for producing a polymethyl methacrylate-based rigid foam according to claim 1, 3. A method for producing a polymethyl methacrylate-based rigid foam according to claim 1, characterized in that the resin is cured in the production of the sandwich member by heating or irradiating in a mold at a temperature above 110°C. 4. The method for producing a polymethyl methacrylate-based rigid foam according to 3 above, characterized in that the resin is cured in an electrically heatable mold. 5. The method for producing a polymethyl methacrylate-based rigid foam according to 3 above, characterized in that the resin is cured using infrared rays. 6. The foam material has a compressive strength of 30 to 500 kg / m, measured according to DIN EN ISO 1183. 3 6. The method for producing a polymethyl methacrylate-based rigid foam according to any one of 1. to 5. above, wherein the foam has a density of 1. 7. Use of a polymethyl methacrylate-based rigid foam in a sandwich component produced according to any one of claims 1 to 6, characterized in that the foam is used as core material in rotor blades of wind power plants or in boat construction, in lightweight construction, as packaging material, as energy absorber in crash elements, in architectural structural elements, as diffuser in lighting engineering applications, in furniture assembly, in vehicle construction, in the aviation industry or in model building.

Claims

1. 1. A process for the production of a polymethyl methacrylate-based rigid foam in sandwich components for use in wind power plants and in boat construction, having a glass transition temperature Tg above 110° C., determined by DMTA measurement according to standard ISO 6721-7, characterized in that a polymer composition with a blowing agent is foamed to obtain a foam material having an average pore size in the range of 50 to 300 μm, measured according to ASTM D3576.

2. The resin absorption of the foam material is between 0.01 and 0.03 g / cm as measured by VARI. 2 2. The method for producing a polymethyl methacrylate-based rigid foam according to claim 1, wherein

3. 2. A method for producing a polymethyl methacrylate-based rigid foam according to claim 1, characterized in that the curing of the resin during the production of the sandwich element is carried out by heating or irradiation in a mold at a temperature above 110°C.

4. 4. The method for producing a polymethyl methacrylate-based rigid foam according to claim 3, wherein the resin is cured in an electrically heatable mold.

5. 4. The method for producing a polymethyl methacrylate-based rigid foam according to claim 3, wherein the resin is cured by using infrared rays.

6. The foam material has a compressive strength, measured according to DIN EN ISO 1183, of 30 to 500 kg / m 3 6. A method for producing a polymethyl methacrylate-based rigid foam according to claim 1, characterized in that the foam has a density of

7. 7. Use of a polymethyl methacrylate based rigid foam in a sandwich component manufactured according to any one of claims 1 to 6, characterized in that the foam is used as core material in rotor blades of wind power plants or in boat construction, in lightweight construction, as packaging material, as energy absorber in crash elements, in architectural construction elements, as diffuser in lighting engineering applications, in furniture assembly, in vehicle manufacturing, in the aviation industry or in model building.